A qualitative study of alcohol, health and identities among UK adults in later life. - Graeme B Wilson; Eileen F S Kaner; Ann Crosland; Jonathan Ling; Karen McCabe; Catherine A Haighton (PLoS ONE)
Increasing alcohol consumption among older individuals is a public health concern. Lay understandings of health risks and stigma around alcohol problems may explain why public health messages have not reduced rates of heavy drinking in this sector. A qualitative study aimed to elucidate older people's reasoning about drinking in later life and how this interacted with health concerns, in order to inform future, targeted, prevention in this group. In 2010 a diverse sample of older adults in North East England (ages 50-95) participated in interviews (n = 24, 12 male, 12 female) and three focus groups (participants n = 27, 6 male, 21 female). Data were analysed using grounded theory and discursive psychology methods. When talking about alcohol use older people oriented strongly towards opposed identities of normal or problematic drinker, defined by propriety rather than health considerations. Each of these identities could be applied in older people's accounts of either moderate or heavy drinking. Older adults portrayed drinking less alcohol as an appropriate response if one experienced impaired health. However continued heavy drinking was also presented as normal behaviour for someone experiencing relative wellbeing in later life, or if ill health was construed as unrelated to alcohol consumption. Older people displayed scepticism about health advice on alcohol when avoiding stigmatised identity as a drinker. Drinking patterns did not appear to be strongly defined by gender, although some gendered expectations of drinking were described. Identities offer a useful theoretical concept to explain the rises in heavy drinking among older populations, and can inform preventive approaches to tackle this. Interventions should engage and foster positive identities to sustain healthier drinking and encourage at the community level the identification of heavy drinking as neither healthy nor synonymous with dependence. Future research should test and assess such approaches.